Plan Of Arundel And Essex Houses. (From An Original Etching By Hollar, Published In Ogilby And Morgan's Twenty-Sheet Plan Of London.) (Tufts Archival Research Center, 2005)
This illustration is from Walter Thornbury "Old and new London, a narrative of its history, its people, and its places, vol. 3"